Pengaruh Person-Job Fit dan Person-Organization Fit terhadap Perilaku Kerja Inovatif dengan Organizational Citizenship Behavior sebagai Variabel Mediasi: Studi pada Karyawan PT Bukit Makmur Mandiri Utama (BUMA) Jobsite - Alya Azahra; Suharnomo Suharnomo (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to analyse the influence of person-job fit and person-organisation fit on innovative work behaviour in the workplace, with organisational citizenship behaviour (OCB) as a mediating variable. Person-job fit and person-organisation fit are used as independent variables, innovative work behaviour as the dependent variable, and organisational citizenship behaviour as the mediating variable. The population in this study comprises all permanent employees at PT Bukit Makmur Mandiri Utama (BUMA), Jobsite GEO-AJE, totalling 1,852 individuals as of November 2024. The sample size was determined using a 5% margin of error, resulting in the selection of 330 respondents through proportionate stratified random sampling. Data were collected via a questionnaire and analysed using Structural Equation Modelling (SEM) with SmartPLS 4.0. The results indicate that both person-job fit and person-organisation fit have a positive and significant effect on innovative work behaviour only when mediated by employees' organisational citizenship behaviour (OCB).